Pemanfaatan Handphone sebagai Alat Pendukung Pembelajaran di Perpustakaan SMP Negeri 18 Sinjai - Nasrullah, Nasrullah; Wanita, Darma; Tawakkal, Tawakkal (Inkunabula: Journal of Library Science and Islamic Information, 2023)
This research discusses the Utilization of Mobile Phones as a Supporting Tool for Learning in the Library of UPTD SMP Negeri 18 Sinjai. The main issues consist of two sub-problems, namely: the utilization of mobile phones as a supporting tool for learning in the library of SMP Negeri 18 Sinjai and the types of applications used in learning media in the library of SMP Negeri 18 Sinjai. This research is a qualitative study using a descriptive approach with primary data obtained through interviews, observations, documentation, and secondary data as a support for the research results as a data collection method. Data processing and analysis techniques are carried out through three stages: data reduction, data presentation, and drawing conclusions, through tests of credibility, transferability, dependability, and confirmability. The results of this research indicate that the use of mobile phones as a learning media in the library of SMP Negeri 18 Sinjai, such as the benefits of using mobile phones in the library after the implementation of the mobile phone utilization program, has shown different results in terms of students' intelligence. Students find it easier to access school assignments, they are more active, and they read more using mobile phones because students can easily access anything through the internet. Second, the types of applications used in learning media in the library of SMP Negeri 18 Sinjai include the Indonesian National Library application (IPUSNAS), Play Book, digital novels/Wattpad, Wordpress, Macca Office 365 account, and WhatsApp, which can be accessed through mobile phones as learning materials in the library. Abstrak Penelitian ini membahas tentang Pemanfaatan Handphone sebagai Alat Pendukung Pembelajaran di Perpustakaan UPTD SMP Negeri 18 Sinjai. Pokok permasalahan terdiri dari dua sub masalah, yaitu: pemanfaatan handphone sebagai alat pendukung pembelajaran di perpustakaan SMP Negeri 18 Sinjai dan jenis aplikasi yang di gunakan dalam media pembelajaran di perpustakaan SMP Negeri 18 Sinjai Penelitian ini merupakan penelitian kualitatif dengan menggunakan pendekatan dekriptif dengan data primer yang diperoleh melalui wawancara, observasi, dokumentasi dan data sekunder sebagai pendukung dari hasil penelitian sebagai metode pengumpulan data. tehnik pengolahan dan analisis data dilakukan dengan melalui tiga tahap, yaitu: reduksi data, penyajian data, dan penarikan kesimpulan, melalui uji creadibility, uji transferability, uji denpandebality, uji confirmability. Hasil penelitian ini menunjukkan bahwa Pemanfaatan handphone sebagai media pembelajaran di Perpustakaan SMP Negeri 18 Sinjai, seperti manfaat penggunaan handphone di perpustakaan setelah diterapkannya program pemanfaatan handphone terbukti hasil yang berbeda dalam hal kecerdasan siswa seperti siswa semakin mudah dalam mengakses tugas sekolah, siswa lebih aktif dan sering membaca menggunakan handphone karena di dalam handphone siswa mudah dalam mengakses apa saja melalui internet. Kedua, jenis aplikasi yang digunakan dalam media pembelajaran di Perpustakaan SMP Negeri 18 Sinjai, yaitu aplikasi Perpustakaan Nasional Repoblik Indonesia (IPUSNAS), Play Book, Novel digital/Wattpad, Wordpress, Akun Macca Office 365, dan Whatsapp yang dapat diakses melalui handphone sebagai bahan untuk pembelajaran di perpustakaan.